Monitoring and Evaluation of Therapy Response in Advanced-Stage Lung Cancer Treated with Systemic Therapy - Ibrahim Syamsuri; Anna Febriani; Laksmi Wulandari; Farah Fatma Wati (Jurnal Respirasi)
Lung cancer is the second most commonly diagnosed malignancy, with the highest mortality rate in the world. In Indonesia, lung cancer ranks third with 34,783 cases, contributing to the highest number of deaths due to cancer. Most patients are diagnosed at an advanced stage, requiring systemic therapy. Therapeutic modalities for lung cancer patients can include surgery, radiotherapy, and systemic therapy, with the choice of therapy determined by the histological type, disease stage, laboratory results, performance status (PS), and comorbidities. This situation requires regular monitoring and evaluation to reduce the symptoms and improve the patient’s quality of life (QoL). Therapy response in systemic therapy patients can be evaluated through subjective, semi-subjective, and objective evaluations. Subjective evaluation involves monitoring QoL, focusing on cancer outcomes, and patients’ well-being. Semi-subjective evaluation consists of monitoring the patient’s weight and PS. Objective evaluation uses imaging equipment, such as computed tomography (CT) scans, fluoroscopy, magnetic resonance imaging (MRI), and positron emission tomography (PET) scans to monitor tumor progression.